Infusing an Occupational Justice Perspective to Technology use in Occupational Therapy Practice - Lenin C. Grajo; Angela K. Boisselle (Scholarworks @ WMU, 2018)
Vital to building best and evidence-based practices in technology use in occupational therapy is the understanding of technology access, the lived experience of clients from diverse backgrounds who use technologies every day, and the understanding of many various factors (e.g., socioeconomic, political, geographical) that may influence the use of and access to technology. In this Letter from the Editors, we want to infuse the notion of occupational justice in the way that we, occupational therapy practitioners, understand and assess the impact of technology use in daily occupational participation.